Changes on the low-temperature oxidation characteristics of coal after CO2 adsorption: A case study - Feng, G.; Wu, Y.; Zhang, C.; Hu, S.; Shao, H.; Xu, Guang; Ren, X.; Wang, Z. (Elsevier, 2017)
© 2017 Elsevier Ltd. Coal spontaneous combustion is a natural hazard during mining. In China, the longwall gob area is the main places that are prone to coal spontaneous combustion due to excessive residual coal in the gob and severe air leakage during underground mine ventilation. Injecting CO 2 into gob has many advantages to prevent fire disaster. However the characteristics of coal low-temperature oxidation after CO 2 injection were rarely studied. In this paper, a temperature programmed test system was adopted to simulate coal spontaneous combustion at low-temperature stage before and after CO 2 adsorption. Compositions and concentrations of gases produced by coal samples from Yiyuan mine in China at different temperatures were analyzed. It is found that with the increase of the temperature, the gas concentration of CO 2 generated from coal before CO 2 absorption, expressed the trend of exponential growth. While the CO 2 concentration after CO 2 absorption, showed the distribution of "V" type on the whole, that is, the CO 2 concentration firstly dropped to the minimum value and then rose up gradually. Before reaching to the temperature corresponding to the minimum concentration of CO 2 , the CO 2 concentration was significantly higher comparing with that before CO 2 absorption. While over that temperature, with the temperature increasing, the CO 2 concentration was obviously lower than that before CO 2 absorption. During the heating oxidation of coal, the gas concentrations of CO and C 2 H 4 showed the increasing tendency with the temperature increasing. However, the initial temperature of CO and C 2 H 4 detected firstly during the coal oxidation process after CO 2 absorption was obviously lower than that before CO 2 absorption, what's more, the concentrations of CO and C 2 H 4 were also obviously lower than that before CO 2 absorption at the same temperature, showing an obvious "hysteresis" phenomenon of inhibiting coal oxidation. The experimental results provided the basis of a method to control the spontaneous combustion of residual coal by injecting CO 2 into the gob. The field test showed that the index gas concentration of CO was reduced sharply and coal spontaneous combustion in the gob was controlled effectively.